Macronutrient deficiency in snap bean considering physiological, nutritional, and growth aspects - de Souza Osório, Christian Rones Wruck; Teixeira, Gelza Carliane Marques [UNESP]; Barreto, Rafael Ferreira [UNESP]; Campos, Cid Naudi Silva; Leal, Aguinaldo José Freitas; Teodoro, Paulo Eduardo; de Mello Prado, Renato [UNESP] (Public Library of Science (PLoS), 2020)
Nutritional deficiencies limit the growth of snap bean plants, therefore knowing the biological mechanisms involved in it is fundamental. This study is aimed to evaluate the damage caused by a deficiency of macronutrients in physiological variables that cause decreased growth and the appearance of visual symptoms in snap bean. Thus, we design a hydroponic system of snap bean cultivation in order to test the effect of macronutrient deficiencies in a controlled environment. The treatments consisted in evaluate the effects of lack of one macronutrient in time. To perform this, we used Hoagland and Arnon solution in its complete formulation (control) or without N, P; K; Mg, Ca or S in each treatment. Physiological, nutritional, and growth analyses were performed when visual deficiency symptoms of each omitted nutrient appeared. Thus, the omissions of N and P in the nutrient solution led to lower accumulations of all macronutrients in the shoot. And the K, Ca, Mg, and S omissions decreased the amounts of K, Ca, Mg, P, and S in the shoot of the snap bean plants when compared with the plants grown in the complete nutrient solution. With the lowest accumulation of macronutrients, the content of photosynthetic pigments and the photosynthetic rate were reduced, with harmful effects on plant growth. Thus, from the losses in dry matter production of the shoot, the order of limiting of macronutrients in bean plants was N < P < Ca < S < Mg < K, with a decrease of up to 86.2%, 80.1%, 51.2%, 46.5%, 25.6%, and 19.3%, respectively. The nitrogen deficiency is more evident, proven by symptoms such as chlorosis in the lower and upper third leaves and necrosis of the lower third leaves.